Thoracofrenolaparotomies - Valls, Alberto; Liard, Washington (Cirugía del Uruguay, 1972)
Thoracofrenolaparotomies are approach incisions of the right and left thoracoabdominal region and lower thorax, pleura and mediastinum, that give a wide light to deep organs: proximal stomach, 3 lower esophagus, spleen, adrenals, kidney, liver, pedicle hepatic,...